Pengaruh Aktifitas Pengembangan Dalam Kegiatan Ekstrakurikuler Futsal Terhadap Tingkat Kebugaran Jasmani Siswa Sekolah Menengah Atas - Bery Naufal Setiaji; Ega Trisna Rahayu; Saepul Ma’mum (Jurnal Ilmiah Wahana Pendidikan, 2023)
The ability of the physical fitness level of futsal extracurricular participants at SMAN 3 Purwakarta is still low, so this study aims to determine the effect of development activities on the level of physical fitness of students at SMAN 3 Purwakarta. The sample in this study were 27 students participating in futsal extracurricular activities at SMAN 3 Purwakarta participating in futsal extracurricular activities. The sampling method used in this study was cluster random sampling. Retrieval of data using a test, with the instrument used in the form of a skills test. The scores obtained from 60 meter sprint, 60 second sit up, vertical jump, 60 second pull up, and 1200 meter run. The data obtained in this study refers to the design used, namely one group pretest posttest design. The analysis of this program used SPSS 22. The results showed that there was a significant influence on development activities on the level of physical fitness as seen from the results of the Sprint 60 Meter pretest with a mean value of 6.62 standard deviation of 1.644 and posttest results with a mean of 6.63 standard deviation of 1.149. The results of the 60 second Pull Up pretest with a mean of 7,250 standard deviation of 4,035 and the results of the posttest with a mean of 11.33 of a standard deviation of 3,784. Sit Up 60 seconds pretest results with a mean of 34,375 standard deviation of 10,520 and posttest results with a mean of 37.63 standard deviation of 3,784. The results of the pretest vertical jump with a mean of 61,458 standard deviations were 11,651 posttest results with a mean of 4.64 standard deviations of 0.579. The results of the 1200 meter pretest run with a mean of 5,065 standard deviations were 11,651 posttest results with a mean of 4,642 standard deviations of 0,579. As well as testing the hypothesis with a significant level (0.05) and the results obtained sig. From testing the hypothesis using the t test where the sig value of the physical fitness test is 0.000 <0.05, it can be concluded that there is an increase in the level of physical fitness in the futsal extracurricular participants at SMAN 3 Purwakarta. and posttest of 0.3043 which is included in the medium category.